The complete chloroplast genome of Paeonia lactiflora Pall. (Paeoniaceae) - Minjee Lee; Jin Hee Park; Jinsu Gil; Jungho Lee; Yi Lee (Mitochondrial DNA. Part B. Resources, 2019)
The complete chloroplast genome sequence of Paeonia lactiflora was obtained by de novo assembly using next-generation sequencing. The circular molecule of the genome constituted of four parts, with 152,731 bp in the complete chloroplast genome, including a large single-copy (LSC) region of 84,402 bp, a small single-copy (SSC) region of 16,969 bp, and two inverted repeat (IRa and IRb) regions of 25,680 bp each. The genome annotation predicted a total of 111 genes, including 77 protein-coding genes, 30 tRNA genes, and 4 rRNA genes. Phylogenetic analysis showed the close taxonomical relationship to P. veitchii.